A meta-analysis of the effects of academic interventions on academic achievement and academic anxiety outcomes in elementary school children. (June 2022) - Fishstrom, Sarah; Wang, Hsuan-Hui; Bhat, Bethany H.; Daniel, Johny; Dille, Jordan; Capin, Philip; Vaughn, Sharon
Abstract: Research has shown that academic anxiety can affect academic performance and emotional well-being. Despite previous research emphasizing the importance of understanding academic anxiety and indicating a strong association between academic performance and academic anxiety, no systematic reviews or meta-analyses have examined the effects of academic interventions on academic and anxiety outcomes. This article reports on a meta-analysis of studies examining academic interventions conducted with elementary students (kindergarten to Grade 6), in which both academic achievement and academic anxiety outcomes were reported. The systematic search yielded 13 studies comprising 1545 participants and revealed statistically significant differences favoring academic treatments over the control for academic achievement outcomes ( g  = 0.63, k  = 11) but no statistically significant benefits for academic anxiety outcomes ( g  = −0.06, k  = 11). The authors caution against drawing strong conclusions due to the heterogeneity in effects and the small number of studies in the extant literature.